Motivations Behind Dreams: Its Linguistic Concept And Behavioral Impact - Kassem Mohmad, Omar Abou Al-Majd Hussain (Ijaz Arabi Journal of Arabic Learning, 2024)
Dreams are a precious window into the human soul, where all the waves of minds, emotions, and cultures are concentrated. On this basis, this study deals with phenomena that affect general human consciousness and even the daily life of Arab students. Therefore, this study used the scientific and professional literature on dreams to identify their relationship to Arab students' engagement in dreaming during sleep and wakefulness and how this influences dream content. The sample for this study is selected from among the undergraduate students of Prince Sattam University, Al-Kharj, after obtaining approval from the university ethics committee. The sample was selected from male and female college students, including the College of Education and Business Administration. A total of 79 students participated in the study. The participants were men and women. The structured questionnaire consists of several derived sleep components, including dream motivation, dream recall, and the effects of dreams on behavior. The researcher obtained a correlation coefficient, proving that the questionnaire's scale and internal consistency are very high for these items. Most dreams were forgotten, and reports of these dreams reflected waking experiences in particular. Based on this data, the researcher concluded that "students' dreams had little impact on academic and general decisions," meaning that dreams did not have much impact on students.